An integrative view of limitations to muscular performance - Dempsey, J A; Babcock, M A (Advances in experimental medicine and biology, 1995)
First we describe the changing site of limitation to maximal O2 transport with increasing fitness in mammals. The capacity for diffusion and airway/parenchymal flow rate and volume are markedly overbuilt in the sedentary subject's lung, but undergo little change with increased training/fitness; accordingly, as demand for O2 transport increases in the highly fit, the limits for maximal diffusion and ventilation are surpassed or met at maximal exercise. Secondly, low-frequency diaphragmatic fatigue occurred with by heavy endurance exercise. This fatigue resulted from increased diaphragmatic work together with the major contribution from the secondary effects of increased locomotor muscle activity; namely, metabolic acidosis and increased requirement for blood flow.